2010
DOI: 10.1038/leu.2010.247
|View full text |Cite
|
Sign up to set email alerts
|

PHF6 mutations in adult acute myeloid leukemia

Abstract: Loss of function mutations and deletions encompassing the PHF6 gene are present in about 20% of T-cell acute lymphoblastic leukemias. Here we report the identification of recurrent mutations in PHF6 in 10/353 adult acute myeloid leukemias (AML). Genetic lesions in PHF6 found in AML are frameshift and nonsense mutations distributed through the gene or point mutations involving the second PHD-like domain of the protein. As in the case of T-ALL, where PHF6 alterations are found almost exclusively in males, mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 31 publications
6
112
1
Order By: Relevance
“…17 Though X-linked and recessive, BFLS may also occur in women. Remarkably, a 13-fold male excess of PHF6 mutated cases in T-ALL and a 7-fold male excess in acute myeloid leukemia have been reported recently, 18,19 implying skewed inactivation of PHF6 mutations, X-homologs in females, or some other unknown mechanism for maintaining PHF6 expression. However, unlike Van Vlierberghe, 18 we observed no male excess of PHF6 mutations in T-ALL patients, and although we were able to confirm the reported excess of adult (18.6%) over pediatric (5.4%) cases of PHF6 mutations in T-ALL, both our estimates were significantly lower than the corresponding estimates of 38.1% and 15.7% in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Though X-linked and recessive, BFLS may also occur in women. Remarkably, a 13-fold male excess of PHF6 mutated cases in T-ALL and a 7-fold male excess in acute myeloid leukemia have been reported recently, 18,19 implying skewed inactivation of PHF6 mutations, X-homologs in females, or some other unknown mechanism for maintaining PHF6 expression. However, unlike Van Vlierberghe, 18 we observed no male excess of PHF6 mutations in T-ALL patients, and although we were able to confirm the reported excess of adult (18.6%) over pediatric (5.4%) cases of PHF6 mutations in T-ALL, both our estimates were significantly lower than the corresponding estimates of 38.1% and 15.7% in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…PHF6 mutations were detected in 38% (16/42) of adult and 16% (14/89) of pediatric T-ALL patients and rarely also in adults with acute myeloid leukemia. 18,19 PHF6 is X-linked, and tumorigenic mutations have been almost exclusively detected in male patients with either T-ALL or acute myeloid leukemia. This gender-bias has been proposed as contributing to the 3-fold higher incidence of T-ALL in males over females.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivating mutations in PHF6 are the cause of B€ orjeson-Forssman-Lehman syndrome (BFLS), an Xlinked intellectual disability (XLID) disorder (Lower et al 2002). Recently, inactivating PHF6 mutations have been identified in ;25%-30% of human T-cell ALLs (Van Vlierberghe et al 2010;Zhang et al 2012) and in 2%-3% of acute myeloid leukemias (AMLs) (Supplemental Table 5; Van Vlierberghe et al 2011;Patel et al 2012;Yoo et al 2012). While the mutational status of PHF6 has been examined in >100 human B-lineage ALLs (Van Vlierberghe et al 2010;Zhang et al 2012), no PHF6 mutations have been observed in these tumors (Supplemental Table 5), suggesting that inactivating mutations do not promote malignant growth in B-ALL.…”
Section: Resultsmentioning
confidence: 99%
“…The PHF6 alterations result in loss of PHF6 expression and are associated with TLX1/3-and TAL1-rearranged ALL. 17,18 The role of PHF6 in leukemogenesis is poorly understood, but the loss-offunction alterations suggest that PHF6 is a tumor suppressor.…”
Section: T-lineage Allmentioning
confidence: 99%